2018
DOI: 10.1007/s00198-018-4633-3
|View full text |Cite
|
Sign up to set email alerts
|

VITamin D and OmegA-3 TriaL (VITAL) bone health ancillary study: clinical factors associated with trabecular bone score in women and men

Abstract: NCT01747447.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(66 reference statements)
0
13
0
1
Order By: Relevance
“…Women in the upper quartile of HbA1c had the lowest TBS values. As TBS measures bone quality and predicts the risk of fracture [ 33 , 34 ], numerous studies in diabetics have shown a decline in TBS that is inversely related to insulin resistance. In our study of a non-diabetic population, we found that women in Q4 of HbA1c had the lowest TBS levels, which was maintained after adjusting for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the upper quartile of HbA1c had the lowest TBS values. As TBS measures bone quality and predicts the risk of fracture [ 33 , 34 ], numerous studies in diabetics have shown a decline in TBS that is inversely related to insulin resistance. In our study of a non-diabetic population, we found that women in Q4 of HbA1c had the lowest TBS levels, which was maintained after adjusting for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Other inconsistent findings shown in previous studies compared to our data may be contributed by the difference in the mean age of the study participants, in addition to the study protocol including the doses and period of intervention. The pathogenesis of age-related bone loss has gained more attention in recent studies 41. It seems to begin after age 30 years and around the age of 40 years 20.…”
Section: Discussionmentioning
confidence: 99%
“…A second study focusing on P1 receptors and bone mass investigated the effect of caffeine (and other risk factors, namely alcohol and smoking) on osteoporosis in men, but also for this trial, no results have been published yet, although the study already ended in 2001. However, in 2018, Goldman and colleagues published data on the effect of alcohol on bone mineral density, which was not related to purinergic receptors [ 227 ]. The role of the P2X5 receptor in bone diseases hints to a promising receptor to regulate bone homeostasis.…”
Section: Future Aspects Of Purinergic Receptors and Their Ligands mentioning
confidence: 99%